Corticosteroid Therapy and the Risk of Kidney Failure in IgA Nephropathy: A Dose- and Ethnicity-Stratified Meta-Analysis of Randomised Controlled Trials - Festi Eliza; Harnavi Harun; Drajad Priyono; Deka Viotra (Sriwijaya Journal of Internal Medicine, 2026)
Background: Corticosteroids are widely used in IgA nephropathy, but their net benefit is contested because the largest trials show both protection against kidney-function decline and excess serious infection; the optimal dose and consistency across ethnic groups are uncertain. Objective: To quantify the effect of systemic corticosteroids on the risk of kidney failure in IgA nephropathy and to explore modification by dose and ethnicity. Methods: Four databases were searched from inception for randomised controlled trials. Risk ratios (RR) were pooled with a DerSimonian–Laird random-effects model and proteinuria as Hedges' g; heterogeneity was assessed with I² and a prediction interval, bias with RoB 2 and the Egger test, and certainty with GRADE. Results: Ten non-overlapping trials (1,153 participants; 104 vs 165 events) were included. Corticosteroids reduced the risk of kidney failure (RR 0.61, 95% CI 0.42–0.90; I² = 21%; p = 0.012), remaining significant under the Hartung–Knapp correction (0.39–0.97); a dose subgroup difference was significant (p = 0.010, larger effect with high-dose regimens). Proteinuria fell moderately (Hedges' g −0.68, −1.00 to −0.35). Serious infection was more frequent with corticosteroids. Conclusion: Corticosteroids reduce kidney failure and proteinuria but increase serious infection; a reduced-dose strategy preserves benefit while improving safety, supporting individualised, risk-stratified use.